2020
DOI: 10.3390/jrfm13060112
|View full text |Cite
|
Sign up to set email alerts
|

What Role Does the Housing Market Play for the Macroeconomic Transmission Mechanism?

Abstract: The main objective is to answer the question: What role does the housing market play for the transmission mechanism and (in particular) is the impact constant over time? The research question also includes analyzing the importance of the housing market for the transmission mechanism. We estimate an eight-variable structural vector autoregression (SVAR) model of the Swedish economy over the period 1993 and 2018 using quarterly data, covering both the internet bubble in 2000 and the financial crises in 2008. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In part, this is a sign of a monetary institution attentive to significant market fluctuations, especially housing prices, which is a factor that directly affects the household economy. To some extent, this finding is consistent with that of Wilhelmsson (2020), but indicates that the central bank reacts to changes in house prices. On the other hand, in lag 11, the central bank's policy rate does affect house prices in a bidirectional Granger causal relationship.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In part, this is a sign of a monetary institution attentive to significant market fluctuations, especially housing prices, which is a factor that directly affects the household economy. To some extent, this finding is consistent with that of Wilhelmsson (2020), but indicates that the central bank reacts to changes in house prices. On the other hand, in lag 11, the central bank's policy rate does affect house prices in a bidirectional Granger causal relationship.…”
Section: Discussionsupporting
confidence: 84%
“…For this reason, the IPSA of the Santiago stock exchange is incorporated into the analysis, given that it is the financial market performance indicator for the national territory, where real estate investment groups, developers and financial institutions themselves participate. A second factor mentioned in the literature by Wilhelmsson (2020) is the monetary policy rate defined, in the case of Chile, by the Central Bank. Associated with this strategy, the amount of money in circulation is also a strategy defined by the Central Bank in the case of Chile, so it has been decided to incorporate this factor into the causality assessment to review whether the Central Bank influences housing prices and how many periods can be identified for these effects to be reflected in prices.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The new findings made in this study are of great value in complementing and refining the driving mechanisms and evolutionary patterns of the housing market inequality. Yi [104], Liu [105], Zhang [106], and Lin [107] argue that there are significant spatial inequalities in housing in urban and provincial regions in China; Zhou [108], Chen [109], Tuofu [110], Dube [111], Liu [112], and Su [113,114] believe that the factors such as level of economic development, city size, industrial structure, blue and green space, landscape, public transportation, and rail transit have a significant impact on housing inequality in China; Zaniewski [115] holds that industrialization driven by the rapid development of the secondary industry is the dominant mechanism leading to housing inequality in socialist countries; Wang [116], Wilhelmsson [117], Cerutti [118], Golob [119], and Bates [120] propose that finance, especially loans, is in a complex causal relationship with housing and even macroeconomic development, which is largely in agreement with the findings in this paper. However, Zhang [121] argues that urbanization is closely related to housing inequality, Liu [122] argues that the pattern of interaction between urbanization and real estate varies across regions and that urbanization has a Granger effect on real estate investment, and Logan [123] argues that income is the core factor affecting housing inequality in China, all of which are different from the findings in this paper.…”
Section: Drive Mechanismmentioning
confidence: 99%
“…In addition, their studies have shown that house prices play an important role in the monetary transmission mechanism. Wilhelmsson (2020) analyzed the effectiveness of the house prices transmission channel in the Swedish economy using the SVAR method. According to the results of the study, monetary policy has both direct and indirect effects through bank loans.…”
Section: Literature Reviewmentioning
confidence: 99%